Peripheral neuropathy in survivors of childhood acute lymphoblastic leukemia - Ramchandren, Sindhu (2009)
Acute lymphoblastic leukemia (ALL) is the most common form of cancer in children. Recent advances in treatment have led to dramatically improved survival rates. Standard ALL treatment includes multiple administrations of the chemotherapeutic drug vincristine, which is a known neurotoxic agent. Although peripheral neuropathy is a well-known toxicity among children receiving vincristine acutely, the long-term effects on the peripheral nervous system in these children are not clear. The objective of this study was to determine the prevalence of neuropathy and its impact on motor function and quality of life (QOL) among children who survived ALL. Thirty-seven survivors of childhood ALL aged 8–18 underwent evaluation for neuropathy through self-reported symptoms, standardized examinations, and nerve conduction studies (NCS). Functional impact of neuropathy was assessed using the Bruininks-Oseretsky test of Motor Proficiency (BOT-2). QOL was assessed using the PedsQL. Nerve conduction study abnormalities were seen in 29.7% of children who were longer than 2 years off therapy for ALL. Most children with an abnormal examination or NCS did not have subjective symptoms. Although overall motor function was below population norms on the BOT-2, presence of neuropathy did not significantly correlate with motor functional status or QOL.